2013
DOI: 10.1021/op400102e
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph Discrimination Using Low Wavenumber Raman Spectroscopy

Abstract: Characterization of crystalline polymorphs and their quantitation has become an integral part of the pre-clinical drug development process. Raman spectroscopy is a powerful technique for the rapid identification of phases of pharmaceuticals. In the present work we demonstrate the use of low wavenumber Raman vibrational spectroscopy (including phonon measurement) for discrimination among polymorphs. A total of 10 polymorphic pharmaceuticals were employed to conduct a critical assessment. Raman scattering in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 28 publications
3
55
0
1
Order By: Relevance
“…Additionally, we focus on correlations within the 0-900cm −1 region only. The fol- [44] and [54]. The shaded areas around the anharmonic spectra indicate the uncertainty derived from the statistical error of the different trajectories.…”
Section: Mode Couplingmentioning
confidence: 99%
“…Additionally, we focus on correlations within the 0-900cm −1 region only. The fol- [44] and [54]. The shaded areas around the anharmonic spectra indicate the uncertainty derived from the statistical error of the different trajectories.…”
Section: Mode Couplingmentioning
confidence: 99%
“…Matzger's group compared the utility of LFRS and conventional Raman spectroscopy for the discrimination of the different phases of ten polymorphic pharmaceuticals including the widely studied model polymorphic API paracetamol [69]. The discriminating power of the LF range was found to be clearly superior to that of the conventional Raman range and to present a fingerprint region for polymorphs.…”
Section: Low-frequency Raman Spectroscopymentioning
confidence: 99%
“…On the other hand, in the case of carbamazepine two of the five known polymorphs, form I and II, have very similar lattice structures and this is reflected in the similarity of their LF Raman spectra. Matzger and coworkers suggested that the LF range could be used to assess packing similarities in the absence of crystallographic data [69]. Very often the combined analysis of the phonon and intramolecular vibrations prove to provide useful complementary information on phase transformations.…”
Section: Low-frequency Raman Spectroscopymentioning
confidence: 99%
“…Based on this notion, low wavenumber Raman spectroscopy and terahertz (THz) spectroscopy has been used for polymorphs discrimination. [13][14][15] Much less work has been conducted in pharmaceuticals with infrared spectroscopy in this low wavenumber region, in spite of the fact that FT-IR is the most common of all vibrational spectroscopies. This apparent paradox can be traced to the typical configuration of mid-IR spectrophotometers which are equipped with window materials that absorb far-IR radiation.…”
Section: Introductionmentioning
confidence: 99%